Evaluation of biological activities of Alpinia mutica Roxb. and its chemical constituents - Mustahil, Noorul Adawiyah; Sukari, Mohd Aspollah; Abdul, Ahmad Bustamam; Ali, Nor Azah; Ee, Gwendoline Cheng Lian (University of Karachi. Faculty of Pharmacy, 2013)
Phytochemicals investigation on rhizomes of Alpinia mutica has afforded five compounds namely 5,6-dehydrokawain (1), flavokawin B (2), pinostrobin (3) and pinocembrin (4) together with β-sitosterol (5). All crude extracts of the plant demonstrated strong cytotoxicity against CEMss (human T4 lymphoblastoid) cancer cells with IC50 values less than 19 µg/mL, while flavokawin B (2) was the most cytotoxic isolate with IC50 value 1.86±0.37 µg/mL. Most of the crude extracts and isolated compounds showed weak activity in antimicrobial and diphenylpicrylhydrazyl (DPPH) radical scavenging activity tests.